2018
DOI: 10.1186/s12889-018-6172-4
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic and demographic predictors of resident knowledge, attitude, and practice regarding arthropod-borne viruses in Panama

Abstract: BackgroundWe sought to identify if socioeconomic and demographic factors play a role in resident knowledge, attitude, and practice regarding Dengue, Chikungunya, and Zika in order to inform effective management procedures for disease prevention in Panama, a middle-income tropical country in Central America. All three are arthropod-borne viruses transmitted by Aedes mosquito vectors present in the focal region of Panama City, the largest city in Central America and an urban region of extreme socioeconomic polar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 62 publications
0
17
1
4
Order By: Relevance
“…They also found that those in higher income brackets had higher knowledge scores. They did not find education to be a predictor of knowledge score for these diseases [13]. In our study community, the results suggest that future campaigns should be aimed at those with lower level of education.…”
Section: Plos Neglected Tropical Diseasescontrasting
confidence: 72%
See 1 more Smart Citation
“…They also found that those in higher income brackets had higher knowledge scores. They did not find education to be a predictor of knowledge score for these diseases [13]. In our study community, the results suggest that future campaigns should be aimed at those with lower level of education.…”
Section: Plos Neglected Tropical Diseasescontrasting
confidence: 72%
“…The results of KAP surveys help create culturally-competent interventions that are specific to the affected community [8]. Recently, in Latin America, KAP surveys have been used to assess knowledge, attitudes, and practices and inform interventions for Dengue, Zika, Chikungunya, and Malaria [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…There is limited information on community knowledge, attitude and practices (KAP) on MBVD in Sub-Saharan Africa [7]. Studies outside Africa have shown that KAP on MBVD vary widely across populations and countries [8][9][10][11][12][13]. Inadequate knowledge is a signi cant barrier for appropriately empowering local communities and individual interventions against MBVD.…”
Section: Introductionmentioning
confidence: 99%
“…Neglected and emerging infectious diseases are the most alarming public health challenges of the twenty-rst century [1][2][3]. Globally, risky areas for pathogen spillover (e.g., disease hotspots) are projected to occur in tropical and developing regions where human population has grown signi cantly, increasing the interactions between wildlife, domestic animals and people, particularly in the context of habitat disturbance, climate change and socioeconomic inequality [4][5][6][7][8]. Lately, the world has seen a rising number of infectious disease threats with alarming consequences.…”
Section: Introductionmentioning
confidence: 99%